Assessing Financial Performance Through Ratio Analysis: A Study on PT Unilever Indonesia Tbk - Buulolo, Florentina; Nopiana, Puspita Rama (Asosiasi Dosen Akuntansi Indonesia, 2025)
The purpose of this research is to analyze financial performance using liquidity ratios (Current Ratio and Cash Ratio), solvency (Debt to Assets Ratio and Debt to Equity Ratio), profitability (Return on Investment and Return on Equity), and activity (Asset Turnover and Fixed Asset Turnover) at PT Unilever Indonesia Tbk. for the period 2019–2024. The research method used is a quantitative descriptive method, which explains and provides an overview of a phenomenon from numerical data listed in the financial statements for 6 consecutive years. The results of the study indicate that PT Unilever Indonesia Tbk. has excellent profitability and asset efficiency, this can be seen from the ROI, ROE, TAT, and FAT values that are above industry standards. However, in terms of liquidity, the Current Ratio is below standard, even though the Cash Ratio is very high. This is due to sufficient cash capacity to meet short-term obligations. Meanwhile, a high solvency ratio indicates the company dependence on debt, so financial risks need to be managed more carefully. This research provides an empirical picture of the strengths and weaknesses of the company financial performance and can be the basis for management strategies in optimizing capital structure, increasing liquidity, and maintaining asset efficiency in a sustainable manner.